Relationships between eating disorder symptoms, muscle dysmorphia symptoms, and suicidal ideation: A random intercepts cross‐lagged panel approach - Grunewald, William; Troop‐Gordon, Wendy; Smith, April R. (The International journal of eating disorders, 2022)
Objective Eating disorder (ED) symptoms correlate with suicidality; yet the strength of these relationships in men is unclear. Muscle dysmorphia (MD) symptoms may reflect a more accurate index of body‐related concerns for men, as they better target muscularity concerns typical of men. However, no studies have tested a model in which ED/MD symptoms and suicidality are simultaneously examined. We longitudinally tested whether ED/MD symptoms were related to suicidal ideation among a community sample of men. Methods Men with MD symptoms (N = 272) were recruited to complete three surveys over 6 weeks. A random intercepts cross‐lagged panel model tested predictive associations between ED/MD symptoms and suicidal ideation, while disaggregating between/within‐person variance. Results ED/MD symptoms were significantly associated with suicidal ideation at the between‐subjects level (ED: b = .04; MD: b = .09) and showed significant within‐wave covariances with suicidal ideation (ED: b = .02–.04; MD: b = .02–.05). Those who experienced increases in ED symptoms showed increased suicidal ideation at the next wave (b = .32). Those who experienced increases in suicidal ideation showed increases in MD symptoms at the next wave (b = .85). Discussion Results highlight ED symptoms as a potential risk factor for suicidal ideation among men. Further, suicidal ideation predicted MD symptoms. ED symptoms may create intra‐ and interpersonal distress predicting suicidal ideation. Suicidal ideation may lead to muscle‐building behaviors to cope with suicidal thoughts. Clinicians should assess for suicidal ideation among men at risk for MD/EDs, and for MD symptoms among those reporting suicidal ideation. Public Significance Eating disorder (ED) symptoms are related to suicidality, but these relationships are understudied among men. Since men report concerns surrounding muscularity, muscle dysmorphia (MD) may be a better ED index for this population. However, little research has investigated relationships between ED symptoms, MD symptoms, and suicidality among men. This study investigated relationships between ED/MD symptoms and suicidality among 272 men. Results may inform clinical assessment, treatment, and classification of MD.